OUTCOME COMPARISON OF LASER-ASSISTED IN SITU KERATOMILEUSIS IN VARIOUS DEGREE OF MYOPIA - Syifa Rahmani (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2023)
Introduction: The femtosecond Laser-Assisted in Situ Keratomileusis (fs-LASIK) procedure iscommonly used for myopia correction because of good efficacy, safety, and predictability. The aim ofthis study was to compare the outcome of the fs-LASIK procedure among myopia groups in CicendoEye Hospital from January to December 2021.Methods: This retrospective study included 212 patients (399 eyes) and the data were obtained frommedical records from January 2021 to December 2021 using ICD-10 coding for LASIK (S0800),consisting of fs-LASIK procedures. The outcome variables were safety index, and efficacy index.Results: The median of safety index was not statistically significant different between groups,1,00(0,50-1,67) in low myopia, 1,00(0,20-1,43) in moderate myopia, and 1,00(0,30-3,33) in highmyopia. The median of efficacy index was statistically significant different between groups, 1,00(0,40-1,67) in low myopia, 1,00(0,20-1,43) in moderate myopia, and 1,00(0,30-3,33) in high myopia. Theproportion of eye with UCVA > 6/12 on the first month after the procedure was higher in the mildmyopia group (223;99,2%) than in moderate myopia (87;98,8%) and high myopia (77;88,5%) withp=0,0001. The proportion of eye with BCVA > 6/12 on the first month after the procedure was alsohigher in the mild myopia group (224;100%) than in moderate myopia (87;98,8%) and high myopia(82;94,3%) with p=0,0001.Conclusion: There was no statistically significant difference of the safety index between groups. Theefficacy index was statistically significant different between groups.Keywords: efficacy index, LASIK, myopia, outcome, safety index